2011
DOI: 10.1017/s1355617711001056
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Examination of Frontal Regions in Boys and Girls with Attention-Deficit/Hyperactivity Disorder

Abstract: The current study examined regional frontal lobe volumes based on functionally relevant subdivisions in contemporaneously recruited samples of boys and girls with and without attention-deficit/hyperactivity disorder (ADHD). Forty-four boys (21 ADHD, 23 control) and 42 girls (21 ADHD, 21 control), ages 8–13 years, participated. Sulcal–gyral landmarks were used to manually delimit functionally relevant regions within the frontal lobe: primary motor cortex, anterior cingulate, deep white matter, premotor regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 56 publications
7
36
1
Order By: Relevance
“…In the only previous VBM study considering potential gender effects, no interaction between gender and diagnosis of ADHD were found, possibly due to the large age range (7-17 years) of the participants included, spanning different brain maturational stages (Yang et al, 2008). Our results are, however, consistent with previous evidence of gender-by-diagnosis interaction in structural brain imaging (Mahone et al, 2011;Dirlikov et al, 2014), electroencephalography (Clarke et al, 2001;Hermens et al, 2004) and functional brain imaging studies of children with ADHD (Ernst et al, 1994;Valera et al, 2010). Thus, our data adds to an increasing number of neuroimaging studies by documenting opposite alterations in brain structure in boys and girls with ADHD, possibly underlying gender-related differences in symptomatology (Hinshaw et al, 2006;Skogli et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the only previous VBM study considering potential gender effects, no interaction between gender and diagnosis of ADHD were found, possibly due to the large age range (7-17 years) of the participants included, spanning different brain maturational stages (Yang et al, 2008). Our results are, however, consistent with previous evidence of gender-by-diagnosis interaction in structural brain imaging (Mahone et al, 2011;Dirlikov et al, 2014), electroencephalography (Clarke et al, 2001;Hermens et al, 2004) and functional brain imaging studies of children with ADHD (Ernst et al, 1994;Valera et al, 2010). Thus, our data adds to an increasing number of neuroimaging studies by documenting opposite alterations in brain structure in boys and girls with ADHD, possibly underlying gender-related differences in symptomatology (Hinshaw et al, 2006;Skogli et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Authors reported no interaction between diagnosis and gender, but several potential confounding factors were present: the study sample was characterized by a large age range (7-17 years), participants presented with various comorbidities, and most patients were receiving medication treatment. Three previous ROI structural studies also examined gender-by-diagnosis interactions in childhood ADHD (Mahone et al, 2011;Qiu et al, 2009;Dirlikov et al, 2014). Two of these studies were restricted to the frontal lobe, manually or automatically delimiting functionally relevant sub regions such as the primary motor cortex, the anterior cingulate cortex, the premotor region, the orbitofrontal cortex or the inferior prefrontal cortex (Mahone et al, 2011;Dirlikov et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional studies have revealed anomalous activations within motor areas in patients with ADHD at a resting state or when performing tasks that require response inhibition or motor control [33,34]. Previous structural study has also found reduced volume of motor areas in ADHD patients [35]. The results of our study are consistent with these previous findings; gray matter volume reductions in the primary motor/premotor cortex of patients with ADHD may demonstrate a critical role of motor structure deficits in the pathophysiology of ADHD.…”
Section: Discussionsupporting
confidence: 91%